Nivolumab monotherapy in metastatic colorectal cancer: current approaches to response evaluation - N. N. Babyshkina; T. A. Dronova; P. A. Gervas; N. O. Popova; A. Yu. Dobrodeev; D. N. Kostromitsky; S. G. Afanasyev; V. E. Goldberg; N. V. Cherdyntseva (Сибирский онкологический журнал)
Aim of the study: a systematic analysis of the modern literature data on the nivolumab monotherapy efficacy in patients with metastatic colorectal cancer (mCRC). Material and methods. The review summarizes the results of clinical studies of the nivolumab efficacy in patients with mCRC between 2012 and 2022. The current approaches to assessing the tumor response in patients treated with immune checkpoint inhibitors are considered, including response patterns and criteria. Results. Data analysis showed that the use of nivolumab in mCRC patients had significant clinical benefits. Nivolumab monotherapy was shown to improve survival in patients with high microsatellite instability (MSI) or deficiencies in mismatch repair (dMMR) that progressed during standard chemotherapy. Numerous clinical studies indicate the atypical response to nivolumab. Traditional response criteria, such as RECIST do not always adequately assess the therapeutic efficacy of nivolumab in patients with mCRC. Conclusion. To improve the efficacy of mCRC treatment, standardized approaches based on the proposed specific criteria for response to immunotherapy, including immune related RECIST, immune RECIST, and immune-modified RECIST must be developed.